Ayurvedic Lifestyle Prescription for Autoimmune Disorder W.S.R. Pemphigus Folliculitis: A Review - Jayshree Hadke1 , Punam Sawarkar2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Summary: Pemphigus folliculitis or Pemphigus foliaceous is one of the autoimmune disorders in whichsuperficial blisters are induced by IgG (mainly IgG4) auto-antibodies which are directed against desmogleini.e. molecule of a cell adhesion, which occurs in the granular layer of the epidermis in Pemphigus folliculitis,this special response as a result of pathogenic & non-pathogenic antibodies produces specific blisters in thislayer of skin. Though it found to be rare in the world’s population, it doesn’t respond satisfactorily withcurrent established treatment. Considering its pathophysiology, lifestyle modification plays an essential rolein its prevention & management. Therefore, this review study is planned with the aim & objective to reviewthe lifestyle modification w.r.s. pathya & Apathya (Ahara & Vihar) for Pemphigus folliculitis with Ayurvedicperspective. Pemphigus folliculitiscan be correlated with Visphotaka (type of Kshudra Kustha Roga) in theAyurvedic perspective. The concerned material related to topic has been reviewed from various modern aswell as Ayurvedic literature,including Samhita and numerous review articles in different journals. Ayurvedai.e. ancient system of medicine described the psychosomatic platform for the healthy lifestyle including thepharmacological and non-pharmacological measures, even for the prevention as well as management forKustha i.e. dermatological disorders,which are always found successful in checking over the pathogenesis ofthis disease. More clinical research studies are expected to prove their efficacy on scientific clinical ground.